1997
DOI: 10.1021/jm9702692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel Rhodacyanine Dyes That Exhibit Antitumor Activity

Abstract: Rhodacyanine dyes and several analogous delocalized lipophilic cations (DLCs) were synthesized and evaluated as novel antitumor agents. Rhodacyanine dye consists of two heteroaromatic rings such as thiazoles at both termini of the conjugate systems and 4-oxothiazolidine (rhodanine) in the middle of it. Compounds with such a unique double-conjugate structure were found to inhibit the growth of several tumor cell lines, such as colon carcinoma CX-1, and to exhibit relatively low toxicity against normal kidney ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…1, Table 1) are close to the typical values for thizolidine-4-one derivatives [6,7,[11][12][13]. In particular, the thiazolidin-4-one cycle is planar and both C(2) C(8) and C(5) C(6) bond lengths are equal to 1.344(4)Å.…”
Section: Molecular Geometry and Crystal Structure Of 3a Andsupporting
confidence: 80%
See 2 more Smart Citations
“…1, Table 1) are close to the typical values for thizolidine-4-one derivatives [6,7,[11][12][13]. In particular, the thiazolidin-4-one cycle is planar and both C(2) C(8) and C(5) C(6) bond lengths are equal to 1.344(4)Å.…”
Section: Molecular Geometry and Crystal Structure Of 3a Andsupporting
confidence: 80%
“…1). The latter type of intramolecular interaction is also typical for the thiazolidin-4-one derivatives [6,7,11]. The nature of the such X S· · ·O contacts is usually explained in terms of the charge transfer from the oxygen lone pair (Lp O ) to the antibonding orbital of the X S bond ( * X S ) [12,13] which is in line with the specific direction of this contact in 3a [C(2)S(1)O (5) is 164.8 (2) • ].…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…b-Hydroxyethyl substituent for R 5 group also lead decrease in activity (6pa versus 6pb). It was observed that counter anion (X Ϫ ) affected antiplasmodial properties to some extent (runs 9,11,12). The difference might be caused by the solubility of the substances in aqueous media.…”
Section: )mentioning
confidence: 99%
“…[9][10][11] Namely, lipophilic cations possessing a delocalized positive charge (DLCs) penetrate the hydrophobic barriers of the plasma and mitochondria membrane in response to the negative inside transmembrane potentials. The higher mitochondrial membrane potentials of carcinoma cells compared to normal cells induce the selective transfer of DLCs into carcinoma mitochondria.…”
mentioning
confidence: 99%